Comparison of selected live organisms and artificial diet as food for the larval rearing of catfish CLARIAS MACROCEPHALUS (Gunther) - Duller-Evangelista, Antonieta T. (CFOS, 1996)
Two feeding trials were conducted to evaluate and compare the effects of feeding live food organisms and artificial diet on the growth and survival of catfish, Clarias macrocephalus larvae.In the first feeding trial, growth was significantly high (P<0.01) in Tubifex sp.-fed larvae (5.1050g and 6.4980cm) and low in all other treatments. However, survival was significantly high (P<0.01) in fish fed Artemia sp.(38.06%) and Moina macroocopa (38.44%). All fish fed artificial diet died after 4 weeks of feeding. In the second trial, there were no significant differences (P>0.01) in weight gain of the larvae fed Tubifex sp. (3.8628g), Artemia sp.(3.7193g), M. macrocopa (3.7156g) and Chironomus sp. (3.6572g). Weigh gain attained by fish fed artificial diet was 2.8565g and that fed with Brachionus calyciflorus attained 2.9202g after 4 weeks. Lenght increment was significantly high (P<0.01) in fish fed Tubifex sp. (2.2480cm) closely followed by fish led M. Macrocopa (2.0547cm) and Artemia sp. (1.9745cm). Length increment of fish in all other treatments was significantly low. Larvae fed Tubifex sp., M. macrocopa and B. calyciflorus (83.44, 79.37% and 74.06% ; respectively) had the highest survival. larvae fed Chironomus (26.25%) and artificial diet (3.1250%) had significantly low survial rates compared with that of Tubifex-fed larvae. The results obtained in both of the 2 feeding trials (1 and 2 combined) showed that growth (weight gain and length increment) and survival was highest in Tubifex (3.6461g, 2.1673cm and 82.03% ; respectively) fed larvae However, no significant differences (P>0.01) was observed in larvae fed Moina (3.5225g, 2.2011cm and 82.62% ; respectively) and Artemia (3.5882g, 1.8974cm and 74.53% ; respectively).